2015
DOI: 10.1093/her/cyv024
|View full text |Cite
|
Sign up to set email alerts
|

Act Healthy: promoting health behaviors and self-efficacy in the workplace

Abstract: Chronic health conditions and multiple health risk factors afflict Americans and burden employers, but effective, affordable, workplace-based health promotion interventions have not been widely implemented. This is the first study to adapt the empirically validated Chronic Disease Self-Management Program for a general employee population in a workplace setting with an emphasis on disease prevention and health promotion. A quasi-experimental, wellness standard of care comparison, prospective cohort design was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
0
25
0
2
Order By: Relevance
“…Mehri et al reported that 53% of all deaths attributed to NCDs globally are related to lifestyle practices (9). Several studies have reported on health-promoting lifestyle of different categories of workers while only few reported on academic staff (15)(16)(17)(18). However, all these studies were conducted in developed countries except one that was conducted in a low middle-income country.…”
Section: Introductionmentioning
confidence: 99%
“…Mehri et al reported that 53% of all deaths attributed to NCDs globally are related to lifestyle practices (9). Several studies have reported on health-promoting lifestyle of different categories of workers while only few reported on academic staff (15)(16)(17)(18). However, all these studies were conducted in developed countries except one that was conducted in a low middle-income country.…”
Section: Introductionmentioning
confidence: 99%
“…Although several worksites do not yet offer comprehensive health-promoting agendas, investigations have archived the ability of workplace programs for superior health outcomes. Funding, staff resources, inconvenient locations, limitation of times, and insufficient employee interest are the barriers to widespread implementation of health-promoting programs, especially, among high-risk employees (Schopp et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, at the individual level, it is important for workers to enhance their self-efficacy, risk perception, and access to information regarding PA community services in their daily working life at their workplace. Both health behavior frequency and self-efficacy have been shown to increase with the installment of a self-management program for a general employee population in a workplace setting ( Schopp et al, 2015 ). Additionally, at a group and environmental level, shifting focus from the problems experienced by each middle-aged worker to that of groups consisting of middle-aged workers or SMEs experiencing the same problems, as well as developing an approach for these groups, are considered effective because of group dynamics ( Paul-Ebhohimhen and Avenell, 2009 ).…”
Section: Discussionmentioning
confidence: 99%